Long-Term Renoprotective Effect of Candesartan in Renal Transplant Patients - Ishii, T.; Yasuda, M.; Itami, Y.; Hayashi, T.; Uemura, H.; Nose, K.; Nishioka, T. (Transplantation Proceedings, 2012)
The renoprotective effects of angiotensin II type 1 receptor blockers (ARBs) have been demonstrated in a number of clinical studies, but there are few evaluations of long-term ARB treatment. We measured blood pressure, urine protein, and estimated glomerular filtration rate (eGFR) among patients under long-term (up to 9 years) treatment with candesartan cilexetil to evaluate its safety and effectiveness to protect renal graft function. This study of 41 patients (31 male and 10 female) who presented with proteinuria and hypertension (blood pressure >140/90 mm Hg) after receiving a renal graft. Their serum creatinine level at baseline was 1.51 ± 0.53 mg/dL. Cyclosporine or tacrolimus were concomitantly prescribed for 18 (43.9%) and 22 (53.7%) subjects, respectively. The ARB treatment period was ≥12 months (up to 9 years, mean 4.8 years). Combination with other antihypertensive drugs (calcium antagonists) was necessary in 14/41 subjects (34.1%). Significant declines in blood pressure were observed during the treatment period; blood pressure reduction target (blood pressure <130/80 mm Hg) was met in 56.1% for systolic and 68.3% for diastolic pressure. No significant increase in serum creatinine level or eGFR was observed. Urinary protein was reduced to negative or marginal in 63.4% of the subjects, demonstrating a significant decrease. Candesartan cilexetil was considered to be safe even for long-term treatment in renal transplant patients, and effective to protect renal graft function.